Thermodynamic equilibrium theory revealing increased hysteresis in ferroelectric field-effect transistors with free charge accumulation - Jasper Bizindavyi (Nature Portfolio, 2021)
The ferroelectric field-effect transistor, which has attracted much attention for application as both a highly energy-efficient logic device and a non-volatile memory device, has often been studied within the framework of equilibrium thermodynamics. Here, the authors theoretically demonstrate the importance of utilizing the correct thermodynamic potential and investigate the impact of free charge accumulation on the equilibrium performance of ferroelectric-based systems.